Analysis Of The Lack Of Air Pressure Generated By The Main Air Compressor No.1 On Board KM.Logistik Nusantara 1 - A Agus Tjahjono; Driaskoro Budi Sidharta; Agam Ramadhan Zapata (Politeknik Transportasi Sungai Danau dan Penyeberangan Palembang, 2022)
Compressor is an auxiliary engine that use to produce pressure air. On ship compressor have important role as compressed air generator because this pressure air use for starting main engine and use for control air on the main engine. As one of auxiliary engine so more attention needed for this compressor for the smooth operation of the ship when sailing. The resulting impact of this lack of air pressure is failure at starting system on main engine. So analysis must be done on compressor as the producer of compressed air to find out the cause of this problem. the most influential component to produce compressed air is lp/hp valve. After knowing the cause of the lack of compressed air produced so maintenance must be do to lp/hp vale so compressed air can be produced without problems.